2012
DOI: 10.1002/acp.2891
|View full text |Cite
|
Sign up to set email alerts
|

Performance in Autobiographical Memory of Older Adults with Depression Symptoms

Abstract: SummaryThe aim of this study was to compare the performance in the Autobiographical Memory Test in older adults with high scores on depression symptoms (HDS) compared with a matched group with low scores on depression symptoms (LDS) according to the clinical cut‐off of the Centre for Epidemiological Studies Depression Scale. Participants were asked to generate specific autobiographical memories in response to a series of positive and negative cue words. Latencies of responses for each item were also scored. LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 57 publications
1
27
1
7
Order By: Relevance
“…Thus, negative mood may activate trait rumination and the negative consequences of rumination on the amount of autobiographical recall can then be observed. In non-depressed older adults, specific autobiographical memory was positively associated with life satisfaction (Latorre et al, 2013) and negatively with hopelessness (Ricarte et al, 2011). Moreover, older adults present a preference for remembering positively rather than negatively valenced information.…”
Section: Rumination Autobiographical Retrieval and Moodmentioning
confidence: 93%
“…Thus, negative mood may activate trait rumination and the negative consequences of rumination on the amount of autobiographical recall can then be observed. In non-depressed older adults, specific autobiographical memory was positively associated with life satisfaction (Latorre et al, 2013) and negatively with hopelessness (Ricarte et al, 2011). Moreover, older adults present a preference for remembering positively rather than negatively valenced information.…”
Section: Rumination Autobiographical Retrieval and Moodmentioning
confidence: 93%
“…However, any memory recovery task, even without being specific, would activate a recall process from a more general stadium which would facilitate in the future a higher number of specific memories that could be employed for positive therapy. In fact, preliminary results in our lab about specific recovery training programs have shown that any recovery activity, even when is not specific, produces an increment in specific recovery (Latorre, Serrano, Ros, Aguilar-Corcoles, & Navarro, 2008). For specificity assessment objectives, the effects of using a higher number of practice words, non-focused on specificity necessarily should be tested.…”
Section: Discussionmentioning
confidence: 99%
“…O que se tem verificado é que, relativamente à especificidade das memórias autobiográficas evocadas, os idosos com sintomatologia depressiva e depressão evocam em média menos memórias autobiográficas específicas em comparação com os idosos sem sintomatologia depressiva e sem depressão (Barata & Afonso, 2012;Birch & Davidson, 2007;Latorre et al, 2013;Ricarte et al, 2011).…”
Section: Memórias Autobiográficas E Sintomatologia Depressiva/ Depressãounclassified
“…Por último, a análise do tempo de latência também tem evidenciado que as pessoas com sintomatologia depressiva apresentam maior tempo de latência que as pessoas sem sintomatologia depressiva (Latorre et al, 2013;Serrano et al, 2007), no entanto no estudo de Birch e Davidson (2007) não foram encontradas diferenças significativas entre grupos.…”
Section: Memórias Autobiográficas E Sintomatologia Depressiva/ Depressãounclassified